Pengaruh Skala Usaha, Umur Usaha, Pengetahuan Akuntansi dan Persepsi Pelaku Usaha Tentang Akuntansi Terhadap Penggunaan Informasi Akuntansi - Desy Trias Anggraeni; Tumirin Tumirin (Journal of Culture Accounting and Auditing, 2022)
This study aims to examine the effect of business scale, age of business, accounting knowledge and perceptions of business actors about accounting on the use of accounting information. This study examines accounting information on Micro, Small and Medium Enterprises (MSMEs) in Gresik Regency using independent variables, namely business scale, business age, accounting knowledge and business actors' perceptions of accounting. The research population is MSMEs registered at the Department of Cooperatives and Trade of Gresik Regency. Sampling using the Simple Random Sampling method with a total sample of 100 respondents. The primary data collection method is a random method. The method of data collection is distributing questionnaires by visiting MSME actors. The data analysis technique used is multiple linear regression analysis. The results of hypothesis testing show that the variables of business scale, age of business, accounting knowledge and perceptions of business actors about accounting have a significant and significant effect on audit quality. Based on these results, the Department of Cooperatives and UMKM is expected to be able to carry out regular counseling to UMKM in order to improve the quality of human resources and individual understanding in order to develop their business, because by increasing these four variables it can develop and optimize users of accounting information that is useful for developing their business.